Preservation of Pancasila Cultural Values by Millennials in The Development of Trends in Globalization Era - Renata Noorawhita (Jurnal Budaya Nusantara, 2021)
Backgrounds: The current stronger current of globalization has created many trends among the millennial generation. Most of the current trends are trends with the "ideology of western countries". This shows that the cultural value of the Pancasila ideology is slowly eroding. Based on these problems, the researcher formulated a question: What is the role of the millennial generation in preserving the cultural values ​​of Pancasila? Purpose: The purpose of this research is to find out the impact of trends that exist among the millennial generation on cultural values, knowing how the millennial generation can do in preserving the cultural values ​​of Pancasila. Methods: the method used in this study is a literature review. A search for journals is done through google. Indirect interviews with Millennials and Observation of content on Social Media. Results: The results of this study indicate the influence of trends in the millennial generation on the cultural values ​​of Pancasila and the extent to which the cultural values ​​of Pancasila are preserved by the millennial generation. Conclusion: The conclusion of this study discusses the role of the Millennials Generation who preserve the cultural values of Pancasila in the midst of trend developments by showing their own way.